PROVENANCE OF KARAKUM DESERT SAND (TURKMENISTAN): LITHIC-RICH OROGENIC SIGNATURE OF CENTRAL ASIAN DUNE FIELDS (Rivista italiana di Paleontologia e Stratigrafia, 2018)
Major deserts do not necessarily consist of eolian dunes as quartz-rich as those of the Great Nafud, Rub’ al Khali, Sahara, and Mega-Kalahari sand seas accumulated in anorogenic settings of Arabia and Africa. The Karakum dune field of Turkmenistan is one of the several examples of central Asian deserts bound by recent or recently reactivated orogenic belts where eolian sand includes abundant sedimentary and subordinately metamorphic and volcanic lithic fragments. Feldspatho-litho-quartzose detrital modes and epidote-amphibole-garnet heavy-mineral suites of southern Karakum dune sand compare well with those in mountain branches of the Amu Darya, indicating provenance from the western Pamir mountains of Tajikistan in the east. Dunes closer to the Caspian Sea in the west contain additional carbonate or felsic volcanic grains which, together with decreasing heavy-mineral concentration and increasing ZTR indices, reveals local recycling of cover strata exposed in the Kopeh-Dagh and Balkhan zone. Our data suggest that the huge Amu Darya River, which in Plio-Pleistocene to historical times has repeatedly changed its course across Turkmenistan from westward toward the Caspian Sea to northward toward the Aral Sea, represents the major sediment source for the Karakum Desert. Together with the Taklamakan sand sea of the Tarim basin, the Ordos and adjacent deserts of northern China, and the Thal and Thar deserts of the western Himalayan foreland basin, the Karakum would thus represent another example of large dune field principally fed by one major fluvial feeder system.